Гурток антропології та передісторії кабінету антропології ім. Ф. Вовка - Яненко, А.С. (Археологія, 2015)
З’ясовується персональний склад практикантів гуртка/семінару антропології та передісторії Кабінету антропології ім. Ф. Вовка, упорядковуються біографічні свідчення про учасників семінару, здійснюється огляд практичних і теоретичних досліджень, які проводили ці молоді вчені. Seminar/circle of anthropology and prehistory of the F. Vovk Cabinet of Anthropology was founded for training the scientific stuff for individual research activity, namely, for field research, was initiated by the youths, research fellows of certain scientific organizations in Kyiv and teachers of Kyiv schools, and was agreed by the Cabinet’s leaders: M.Ya. Rudynskyi and A.Z. Nosov. The first organizational meeting of the seminar took place in 28 December 1927. The circle included the following members during the period of its functioning from 1927 to 1934: N.V. Romanenko, O.I. Vorobiyeva, L.E. Kistiakivskyi, K.P. Starzhevskyi, M.S. Mushket, N.I. Broyakovska, I.H. Vlasenko, A.M. Voronyi, M.P. Tkach, V.Kh. Shevchenko, A.V. Yakubskyi, O.I. Zinevych, and N.A. Berehova. Individual dimension of the anthropological and prehistoric seminar are the destinies of its students, representatives of intellectual archaeological community of the USSR. Biographic mostly scanty information about more than a decade of archaeologists/anthropologists having related their lives with homeland academic and museum organizations testify that the circle became a place of professional development of the young scholars where they received theoretical knowledge and skills, improved the methods of archaeological and anthropological research, got acquainted with the museum technology, conducted their own field research, discovered the new monuments, and published the results of their scientific research. It is noteworthy, that some students studied in the Kyiv Archaeological Institute which liquidation led to the need of creating the new forms of preparing the qualified stuff. The circle of anthropology and prehistory, together with the seminars and post-graduate studies in the museums and scientific and research departments of the Ukrainian Academy of Sciences became one of such forms and a platform for the professional development and for communication between both the beginners, and experienced scholars. The destinies of most of the seminar members who obtained the practical experience and theoretical knowledge remain unascertained. However, taking into consideration that, at the beginning of the 1930s, the struggle for Marxist’s principles establishing in archaeological research, for «Marrism»/Japhetic ideology implementation, the criticism against «bourgeois and nationalism» scholars and their scientific achievements started and quickly transformed into repressions against the scientific intellectuals, it can be presumed that vast majority of the seminar members were subjected to repressions. Additional evidence for this presumption is the tragic fates of M.Ya. Rudynskyi (arrested and banished in 1934), A.V. Yakubskyi (arrested in 1937), M.S. Mushket (executed in 1938), and M.P. Tkach (banished). Семинар/кружок антропологии и предыстории Кабинета антропологии им. Ф. Вовка для подготовки научных кадров к самостоятельной исследовательской работе, в частности к экспедиционным исследованиям, был основан по инициативе молодых сотрудников некоторых научных учреждений Киева, преподавателей киевский школ и при согласии руководства Кабинета — М.Я. Рудинского и А.З. Носова. Первое организационное собрание семинара состоялось 28 декабря 1927 г. В состав кружка за весь период его существования (1927—1934) входили: Н.В. Романенко, О.И. Воробиева, Л.Е. Кистяковский, К.П. Старжевский, М.С. Мушкет, Н.И. Брояковская, И.Г. Власенко, А.М. Вороной, М.П. Ткач, В.Х. Шевченко, А.В. Якубский, О.И. Зиневич, Н.А. Береговая. Личностное измерение семинара антропологии и предыстории — это судьбы его практикантов — представителей интеллектуального археологического сообщества УССР. Биографические сведения, преимущественно отрывочные, более десяти археологов/антропологов, которые связали свою жизнь с отечественными академическими и музейными учреждениями, свидетельствуют, что кружок стал местом профессионального становления молодых ученых, где они получали теоретические знания и навыки, совершенствовали методику археологических и антропологических исследований, знакомились с музейной техникой, проводили самостоятельные экспедиционные изыскания, открывали новые памятники, публиковали результаты своих научных исследований. Показательно, что некоторые практиканты обучались в Киевском археологическом институте, ликвидация которого привела к необходимости создания новых форм подготовки квалифицированных кадров. Кружок антропологии и предыстории, наряду с семинарами и аспирантурами при музеях и научно-исследовательских кафедрах ВУАН/УАН, стал одной из таких форм, платформой профессионального роста и коммуникации и для начинающих, и для опытных ученых. Судьба большинства членов семинара, которые получили практический опыт и теоретические знания, остается невыясненной. Однако учитывая, что в начале 1930-х гг. началась борьба за установление марксистских принципов археологического исследования, внедрение «марризма»/яфетидологии, критика «буржуазно-национальных» ученых и их научных достижений, которые быстро приняли формы репрессивных действий против научной интеллигенции, можно предположить, что подавляющее большинство участников семинара были репрессированы. Дополнительное подтверждение этому предположению — трагическая судьба М.Я. Рудинского (арестован и выслан в 1934 г.), А.В. Якубского (арестован в 1937 г.), М.С. Мушкет (расстреляна в 1938 г.), М.П. Ткача (выслан).